The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.18295/squmj.2020.20.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy Levels Regarding Interprofessional Learning Skills Among Undergraduate Healthcare Students in Malaysia

Abstract: Objectives: Self-efficacy is an important factor in determining the ability of students to execute tasks or skills needed in the implementation of interprofessional learning (IPL). This study aimed to identify levels of self-efficacy with regards to IPL skills among undergraduate healthcare students and to investigate differences according to gender, programme of study and year of study. Methods: This descriptive cross-sectional study was conducted between January and March 2018 at the International Islamic Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…This finding has been supported by similar findings in other studies in the literature, including those conducted by the GSS creator. 11 , 25 However, the results of the current study contradict the results of a study which found that final-year male dental students to have higher self-efficacy scores than final-year female dental students. 32 …”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…This finding has been supported by similar findings in other studies in the literature, including those conducted by the GSS creator. 11 , 25 However, the results of the current study contradict the results of a study which found that final-year male dental students to have higher self-efficacy scores than final-year female dental students. 32 …”
Section: Discussioncontrasting
confidence: 95%
“…Self-efficacy is another factor that has been proven to be related to the academic performance, motivation, and learning outcomes of undergraduate health care students. 11 , 12 , 13 , 14 This term refers to individuals’ perceptions of their own competency regarding the performance of a skill or task. 15 It has been suggested that individuals’ levels of self-efficacy affect their performance of tasks.…”
Section: Introductionmentioning
confidence: 99%
“…The CSWE Educational Policy and Accreditation Standards hold that social workers engage in interprofessional collaboration to assess, intervene, and evaluate individuals, families, groups, organizations, and communities (CSWE, 2022). IPE has been instrumental in helping develop students' knowledge, skills, and values (Cramer et al, 2019), self-efficacy (Keshmiri & Ghelmani, 2023;Nurumal et al, 2020;Williams et al, 2017), communication skills (Bell et al, 2019;Kermani et al, 2022), and interprofessional collaboration (Adamson et al, 2020;Kermani et al, 2022;Rubin et al, 2020;Testa & Renwick, 2020;Wilson et al, 2021) that lead to improved health outcomes (Cramer et al, 2019;McKinlay et al, 2019;Pittenger et al, 2019). In addition, students can acquire greater knowledge of their own discipline while learning and understanding the professional roles and responsibilities of other professionals as part of an interprofessional healthcare team (Bridges et al, 2011;van Diggele et al, 2020).…”
Section: Interprofessional Education (Ipe)mentioning
confidence: 99%
“…Consequently, self-efficacy is seen to be essential for successful development among people aiming to become health professionals (2). Self-efficacy refers to an individual's impression of their own competence in doing a skill or task, contributing significantly to the individuals' learning outcomes, especially in undergraduate interprofessional healthcare (3). Moreover, self-efficacy can be considered as one of the significant motivational factors associated with healthcare students' progress (4).…”
Section: Introductionmentioning
confidence: 99%